The Effect of Steam Approach to Economics Media Based on Bima Local Wisdom in Elementary Schools - Mawaddah, Ida; Wahyono, Hari; Andayani, Endang Sri; Sumarsono, Hadi (Journal of Ecohumanism, 2024)
The purpose of this article is to contribute new learning concepts about critical thinking in social sciences, especially economics, as well as the belief that social character is not developed in Indonesian schools. We investigated how primary school teachers self-reported applying what they had learned about economics to their daily social views. With the aid of educational media, this experimental study aimed to ascertain the extent to which the STEAM method influences the meaning of studying economics from early in life. According to the findings, very few pupils comprehend how economics affects both the environment and them in day-to-day living. Not only did we discover that the STEAM technique had a significant effect on pupils' thinking processes. However, they also discover the impact of their characters. There are significant differences in the level of understanding of learning, one of which is influenced by local wisdom. The implications of these findings for sharpening primary school pupils' comprehension of social science courses are explored. We suggest that social science learning be implemented using many of the latest approaches. Focusing on improving character based on local culture is not enough to use the traditional approach that has been implemented so far.